Complete mitogenome of Intermediate Egret Ardea intermedia (Ciconiiformes: Ardeidae). Issue 2 (2nd January 2017) - Tu, Feiyun; Tang, Shan; Yan, Chaochao; Huang, Xiaofeng
Abstract: The Intermediate Egret Ardea intermedia belongs to family Ardeidae, and it is widely distributed over east Africa across the Indian subcontinent to Southeast Asia and Australia. In the present study, the total mitochondrial genome of A. intermedia was determined. The genome is 18, 578 bases in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA genes, 2 ribosomal RNA genes and 2 non-coding regions (CR and CRR), with a base composition of A 30.8%, G 14.0%, T 24.3% and C 30.9%. The dn/ds values of ten PCGs (ND1, ND2, ATP8, ATP6, Cox3, ND3, ND4L, ND4, ND5 and ND6) are below 1. Bayesian inference (BI) and maximum likelihood (ML) methods generated similar topologies. Phylogenies showed that Ardea novaehollandiae and A. intermedia should be assign to Egretta and Ardea, respectively. The mitogenomic data of A. intermedia will be useful in the conservation genetics and phylogeny of the species.